O método pilates como recurso no aumento da flexibilidade e resistência muscular - MARQUES, Cleudiane Dias (2024)
Introdutivo: The Pilates method has been recognized as a practice that improves physical conditioning, promotes rehabilitation, and offers aesthetic benefits, in addition to contributing to mental and physical well-being. This study aims to highlight the effectiveness of Pilates in increasing flexibility and muscular endurance. Objective: To analyze the effects of the Pilates Method on increasing flexibility and muscular endurance based on a systematic literature review. Method: The systematic review utilized databases such as Medline, Scielo, Lilacs, Google Scholar, and UFMA repositories, with studies from 2000 to 2024 in English, Portuguese, and Spanish, using keywords such as "Pilates Method," "localized muscular resistance," and "flexibility." The keywords were combined using Boolean operators (AND, OR, NOT). Results: Pilates was effective in improving flexibility and muscular endurance in various populations, including the elderly, young women, athletes, and clinical patients. It contributes to fall prevention, improves physical performance, and alleviates muscle pain. However, variability in protocols and the lack of control groups limit the generalization of the results. Future research should focus on consistent protocols and larger sample sizes. Conclusion: Pilates has proven effective in improving muscle flexibility, connective tissue elasticity, and muscular endurance. As a complement to conventional training, it offers unique benefits such as enhanced mobility and injury prevention, being accessible and adaptable to different profiles. Regular practice contributes to a better quality of life, proving its relevance as a therapeutic and preventive tool.